Phytocompounds from the Medicinal and Dietary Plants: Multi-target Agents for Cervical Cancer Prevention and Therapy - Shoaib, Shoaib; Islam, Najmul; Yusuf, Nabiha (Current Medicinal Chemistry, 2022)
Cervical cancer is the fourth leading cause of cancer death among women worldwide. Due to cervical cancer's high incidence and mortality, there is an unmet demand for effective diagnostic, therapeutic, and preventive agents. At present, the preferred treatment strategies for advanced metastatic cervical cancer include surgery, radiotherapy, and chemotherapy. However, cervical cancer is gradually developing resistance to chemotherapy, thereby reducing its efficacy. Over the last several decades, phytochemicals, a general term for compounds produced from plants, have gained attention for their role in preventing cervical cancer. This role in cervical cancer prevention has garnered attention on the medicinal properties of fruits and vegetables. Phytochemicals are currently being evaluated for their ability to block proteins involved in carcinogenesis and chemoresistance against cervical cancer. Chemoresistance to cancer drugs like cisplatin, doxorubicin, and 5-fluorouracil has become a significant limitation of drug-based chemotherapy. However, the combination of cisplatin with other phytochemicals has been identified as a promising alternative to subjugate cisplatin resistance. Phytochemicals are promising chemo-preventive and chemotherapeutic agents as they possess antioxidant, anti-inflammatory, and anti-proliferative potential against many cancers, including cervical cancer. Furthermore, the ability of the phytochemicals to modulate cellular signaling pathways through up and down regulation of various proteins has been claimed for their therapeutic potential. Phytochemicals also display a wide range of biological functions, including cell cycle arrest, apoptosis induction, inhibition of invasion, and migration in cervical cancer cells. Numerous studies have revealed the critical role of different signaling proteins and their signaling pathways in the pathogenesis of cervical cancer. Here, we review the ability of several dietary phytochemicals to alter carcinogenesis by modulating various molecular targets.
Keywords: apoptosis